Registro de Polistes simillimus Zikán, 1951 (Hymenoptera, Vespidae) na dieta de Gonyleptes atrus Mello-Leitão, 1923 (Opiliones) - Rubim, Luis G. T. (2022)
Harvestmen are relevant in the food chains of different terrestrial ecosystems, including agricultural systems. In this sense, this work presents new information about the use of social wasps, Polistes simillimus Zikán, 1951 in the diet of Gonyleptes atrus Mello-Leitão, 1923. The recording was carried out at random, on May 31, 2022 in a semideciduous seasonal forest, phytophysiognomy of the Atlantic Forest, in the Parque Nacional do Iguaçu, municipality of Foz do Iguaçu, Paraná, southern Brazil. This record incorporates new information about the diet of Gonyleptes atrus.